2018
DOI: 10.1200/jgo.18.00028
|View full text |Cite
|
Sign up to set email alerts
|

Standard Chemoradiation and Conventional Brachytherapy for Locally Advanced Cervical Cancer: Is It Still Applicable in the Era of Magnetic Resonance–Based Brachytherapy?

Abstract: PurposeRecent guidelines recommend magnetic resonance imaging–based brachytherapy (MRBT) for locally advanced cervical cancer. However, its implementation is challenging within the developing world. This article reports the outcomes of patients with locally advanced cervical cancer treated with chemoradiation and point A–based brachytherapy (BT) using x-ray– or computed tomography–based planning.MethodsPatients treated between January 2014 and December 2015 were included. Patients underwent x-ray– or computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A rate of RT use of 85% was estimated based on available data on incidence of cervical cancer according to stage. 7,8 External radiation fractions needed were calculated on the basis of 25 common fraction schedules as follows: total number of fractions needed for each state = cervical cancers in the state × 0.85 × 25. Presuming that patients with LACC will need four fractions of BT, the overall BT fractions needed were estimated as: cervical cancer cases in state × 0.85 × 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rate of RT use of 85% was estimated based on available data on incidence of cervical cancer according to stage. 7,8 External radiation fractions needed were calculated on the basis of 25 common fraction schedules as follows: total number of fractions needed for each state = cervical cancers in the state × 0.85 × 25. Presuming that patients with LACC will need four fractions of BT, the overall BT fractions needed were estimated as: cervical cancer cases in state × 0.85 × 4.…”
Section: Methodsmentioning
confidence: 99%
“…Because most women with cervical cancer in India (as well as in other low-income countries) present with locally advanced–stage disease, the overall need (in both adjuvant and definitive settings) is expected to be as high as 85% to 90%. 7,8,11,12 However, it is unclear if all women with cervical cancer have access to external-beam radiotherapy (EBRT; also known as teletherapy) or BT. A recent analysis reported that overall, only 35% to 40% of patients in India might have access to RT; however, no specific details are available for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy including brachytherapy forms an indispensable part of the curative management of LACC [9]. Even in FIGO stage IIIB-IVA, local control outside the setting of a clinical trial can be as high as 85% [10], which is unprecedented in locally advanced squamous carcinomas originating at other sites. However, there are several challenges in achieving this, especially in LMICs, including India, in terms of resources, logistics and expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Poor compliance and enhanced acute toxicity are reported in patients from a rural and underprivileged background in LMICs [34]. Audits from developing countries report 42e85% compliance to planned chemoradiation schedules, with a substantial majority of patients receiving less than five cycles of concurrent chemotherapy [29,35,36]. The coexistence of HIV infection within high incidence regions is also associated with reduced odds of receiving concurrent chemotherapy.…”
Section: Access and Delivery Of Concurrent Chemotherapy For Cervical mentioning
confidence: 99%
“…Institutions within LMICs/LICs that have access to brachytherapy infrastructure report waiting lists, with treatment times extending beyond 8 weeks. High volume centres often carry out four to eight brachytherapy procedures per day, making it challenging to carry out state of the art MRI-guided brachytherapy for all-comers [35]. Cost-effective and time-efficient alternatives to MRI brachytherapy include the use of ultrasound and computed tomography for target delineation [52e58].…”
Section: Access To Brachytherapy For Cervical Cancermentioning
confidence: 99%